Optimalisasi Kader Posyandu Kelurahan Bangun Rejo Pembuatan Produk Makanan Tambahan Seblak (Sehat, Bergizi, Lahap, Enak) - Putrawansyah, Ferry; Syahri, Riduan; Padya, Inka Rizki (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The provision of supplementary feeding at community health posts aims to support adequate nutrition for toddlers. However, limited government funding poses challenges for posyandu cadres. To overcome this, cadres conduct self-funding initiatives, even though most of them are housewives. This community service activity aims to assist cadres in developing a provision of supplementary feeding production enterprise through education, capital support, and business mentoring. The stages include preparing health media, conducting health education, forming a management team, producing provision of supplementary feeding, and evaluating business progress. The activity involved 12 cadres from Bangun Rejo Village. The results showed increased knowledge among cadres in producing nutritious, locally sourced provision of supplementary feeding, along with improvements in toddlers’ nutritional status: severe malnutrition decreased from 25% to 10%, moderate malnutrition from 75% to 50%, and good nutrition increased from 0% to 40%. This demonstrates that PMT effectively improves toddlers’ nutrition.